Targeting L-Proline Uptake as New Strategy for Anti-chagas Drug Development - Fargnoli, Lucía; Panozzo-Zénere, Esteban A.; Pagura, Lucas; Barisón, María Julia; Cricco, Julia A.; Silber, Ariel M.; Labadie, Guillermo R. (Frontiers in Chemistry, 2020)
L-Proline is an important amino acid for the pathogenic protists belonging to Trypanosoma and Leishmania genera. In Trypanosoma cruzi, the etiological agent of Chagas disease, this amino acid is involved in fundamental biological processes such as ATP production, differentiation of the insect and intracellular stages, the host cell infection and the resistance to a variety of stresses, including nutritional and osmotic as well as oxidative imbalance. In this study, we explore the L-Proline uptake as a chemotherapeutic target for T. cruzi. A novel inhibitor has been proposed containing the amino acid with a linker and a variable region able to block the transporter. A series of sixteen 1,2,3-triazolyl-proline derivatives have been prepared for in vitro screening against T. cruzi epimastigotes, trypanocidal activity and proline uptake assays. We successfully obtained inhibitors that are able to interfere with the amino acid uptake, which validated our design targeting a metabolite's transport. Additionally, we designed and prepared a fluorescent analogue of the inhibitors that were successfully incorporated by T. cruzi, allowing following up their intracellular fate. This is one of few examples of amino acid transporter inhibitors, being the first case where the strategy is applied on the development of chemotherapy against Chagas disease. This work opens a new horizon on the development of metabolite transporters inhibitors as anti-infective and another chemotherapeutics.